Construction Study on Rodalink Showroom Building: Studi Konstruksi Baja pada Bangunan Gedung Showroom Rodalink - Isda, Is'datul Rofikoh; Safrin Zuraidah; K. Budi Hastono (Universitas Negeri Surabaya, 2025)
The Rodalink showroom is an existing four-story building constructed of reinforced concrete. To compare the different material requirements, a construction study of this building was conducted using a steel structure based on SNI 1729:2020. First, the steel structure was modeled using AutoCAD, then the structural analysis was carried out with the ETABS program. The steel structure consists of main beam elements namely WF 350.175.6.9, WF 350.175.7.11, WF 350.250.9.14, and WF 350.250.8.12. For the sub-beams, the optimal profile is WF 300.200.8.12, while for the column profile is WF 400.300.10.16, and for the X-bracing component is WF 300.200.8.12. The material cost comparison shows that the steel structure portal is 95.45% more expensive with a total cost of IDR 826,467,401 compared to the concrete structure portal of IDR 422,863,490. The high cost of steel structure materials is due to the high cost of production and raw materials, complex manufacturing processes, and additional protection required to prevent corrosion. The price does not include labor costs. Concrete construction takes longer than steel construction, so the potential labor costs for concrete structures tend to be higher.